Perlindungan Hukum terhadap Anak Korban Pelecehan Seksual dalam Perspektif Penegakan Hukum: Analisis Putusan Nomor 2/Pid.Sus-Anak/2025/Pn Bgl - Darma, Rassel Surya; Prasetyo, Boedi (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This study examines the legal protection afforded to child victims of sexual abuse under Indonesia’s Child Protection Law and its implementation in Court Decision Number 2/Pid.Sus-Anak/2025/PN Bgl. National legislation mandates that the state provide special protection for children who become victims of sexual violence, including legal enforcement, psychological assistance, confidentiality safeguards, and comprehensive recovery measures. Analysis of the decision shows that the Panel of Judges applied Article 76D in conjunction with Article 81 of the Child Protection Law and Article 64 of the Criminal Code consistently, including the use of intent doctrines to establish deception and inducement by the perpetrator. The judicial reasoning reflects the principle of the best interests of the child, both in protecting the victim and ensuring proportionate criminal responsibility for the child perpetrator within the framework of the Juvenile Justice System Law. The decision demonstrates a victim-oriented approach, with careful evaluation of evidence and clear recognition of the victim’s vulnerability in repeated acts of sexual intercourse.